Evaluating scenarios of landscape change for Sunda clouded leopard connectivity in a human dominated landscape. (June 2018) - Hearn, Andrew J.; Cushman, Samuel A.; Goossens, Benoit; Macdonald, Ewan; Ross, Joanna; Hunter, Luke T.B.; Abram, Nicola K.; Macdonald, David W.
Abstract: The forests of Borneo support some of the highest biodiversity in the world, yet have experienced among the world's highest rates of deforestation. Such rapid forest loss and associated fragmentation reduces the availability of suitable habitat for wildlife and creates dispersion barriers. Understanding the prevalence and impacts of this anthropogenic disturbance, and developing ways in which to mitigate such changes, is thus critical to the conservation of Borneo's wildlife. Here, we applied a path selection function with conditional logistic regression and used it to develop a resistance surface for a population of Sunda clouded leopards ( Neofelis diardi ) residing within a fragmented and human dominated landscape in Malaysian Borneo. We used cumulative resistant kernel and factorial least-cost path analysis to predict how connectivity may change in response to four future scenarios involving conversion of remaining unproductive forest to palm oil plantations, conversion of unproductive palm oil back to forest, and restoration of a riparian buffer zone along the river, and combination of the two forest restoration scenarios. We showed that Sunda clouded leopard movement is facilitated by forest canopy cover and resisted by non-forest vegetation, particularly recently cleared/planted and underproductive (flooded) plantation areas with low canopy closure. By combining resistant kernel and factorial least-cost path modelling we mapped core areas and the main linkages among them, and identified several key pinch points that may limit regional connectivity of the population. We predict that Sunda clouded leopard connectivity in the region can be greatly enhanced through the protection of privately owned forest patches and the reforestation of underproductive oil palm plantation areas, and creation of a forested buffer zone along the river. Conversely, we show that if the region's unprotected forests were to be converted to plantations then connectivity across the Kinabatangan floodplain would be significantly reduced.